(untitled) (LEARNing Landscapes, 2018)
This study explores the implementation of technology to facilitate students’ persuasive writing skills within elementary school classrooms. Five teachers were interviewed regarding their experiences teaching persuasive writing to students using technology-mediated feedback. Teachers perceived the influence of technology on students’ persuasive writing, on their own teaching practice, and on students’ experiences as valuable for skill development for both themselves and for their students. However, students’ unfamiliarity with technology was at times a hindrance.